Reduction of subsurface acidity in soil column - Chaves, Júlio C. D.; Pavan, Marcos A.; Miyazawa, Mario (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse experiment was conducted for a year with columns to evaluate the influence of subsurface acidity of a dystrophic Latosol Roxo (Oxisol), on the root and shoot growth of coffee. Experiment involved CaCO3 - surface, CaCO3 0 cm - 60 cm, CaCO3 0 cm - 30 cm, CaCO3 30 cm - 60 cm, MgCO3 30 cm - 60 cm, CaSO4 - surface and control. Low soil pH and high Al restricted root and shoot growth of coffee. Surface-applied lime was not efficient either reducing subsoil exchangeable Al or increasing Ca levels in the underlayers of soil. Liming at 0 cm - 30 cm, 0 cm - 60 cm and 30 cm - 60 cm deep, increased soil pH and exchangeable Ca and Mg and decreased exchangeable Al in the applied soil layer only. Gypsum increased the movement of Ca and reduced the exchangeable KCl-Al in the entire soil column. Liming increased N-mineralization and anions leaching and decreased heavy metals leaching. Gypsum increased anions and basic cations and decreased heavy metals leaching. Deep lime applications increased Ca uptake and decreased P, K and Mn uptake. The effects of treatments on shoot growth and leaf area were as following: CaCO3 - 0 cm - 60 cm > CaCO3 0 cm - 30 cm > CaSO4 - surface > CaCO3 - surface > CaCO330 cm - 60 cm = MgCO3 30 cm - 60 cm = control. Regarding root growth, the only difference was that CaSO4 - surface > > CaCO3 0 cm - 30 cm. It was found that gypsum improved deeper root growth as a consequence of the increased movement of Ca and reduction of exchangeable Al in the subsurface of soil.